Cross-Layer Device Authentication with Quantum Encryption for 5G Enabled IIoT in Industry 4.0 - Xu, Dongyang; Yu, Keping; Ritcey, James A. (IEEE transactions on industrial informatics, 2022)
Industrial Internet of Things (IIoT), a core enabler of Industry 4.0, is evolving rapidly to tackle the challenges imposed by explosive real-time manufacturing data in the context of Internet and telecommunication industry. 5G technology is the key to addressing such challenges. This is done by bypassing upper authentication protocols and supporting small data transmission during initial access, which however causes serious security breaches in IIoT device authentication. To solve this, we in this paper propose a secure cross-layer authentication framework based on quantum walk on circles. The system performs random hash coding on multi-domain physical-layer resources to encode and decode device identifiers securely, while using a quantum walk based privacy-preserving protocol to maintain code privacy at arbitrary high level, being controlled by the number of occupied physical resources. The upper bound of decoding errors is derived and a non-convex integer programming problem of minimizing the bound is formulated to characterize the security performance. The space of one-time keys for encryption is also derived that show how high privacy and scalability advantage is maintained against classical and quantum computers. Finally we derive novel expressions of failure probability of this new authentication system and numerically show that our scheme can bring ultra-high level of security and privacy protection with low latency despite attack.